FRI0632 Impact of a tight control multidisciplinary rheumatology program on the quality of life of patients with autoinmune diseases in colombia. (12th June 2018) - Pineda-Tamayo, R.; Alzate, M.-A.; Hernandez-Parra, D.; Echeverry, D.; Ortiz-Salazar, P.; Rojas-Villarraga, A.
Abstract : Background: Autoimmune diseases are chronic inflammatory pathologies of complex etiology and variable clinical expression that usually affect young individuals, generating chronical pain and altering their functionality. Therefore, one of the mainstays of the treatment is to improve the quality of life (QoL) of these patients Objectives: To determine the impact of a tight control multidisciplinary rheumatologyprogram in the QoL of patients with rheumatoid arthritis (RA), Systemic lupus erythematosus (SLE) and seronegative spondyloarthropathies (SpA). Methods: A analytical quasi-experimental study was conducted were 3812 patients with RA, 590 patients with SLE and 605 patients with SpA were included and followed between February 2015 and December 2016. Two separated measurements of QoL were developed through the EuroQol Five Dimensions Questionnaire (EQ-5D) by time trade-off (TTO) valuation technique and the visual analogue scale valuation technique (EQ-VAS). Sociodemographic characteristics were analyzed with univariate statistic. The impact on QoL was determined by McNemar test and repeated measures analysis of variance (rANOVA) Results: The most affected dimensions of the EQ-5D were pain/discomfort and anxiety/depression, while the least affected was self-care. When comparing each dimension before and after the entry to the tight control program, a significant increase in the proportion of patients that perceive level 1 for each aspect evaluated was found. In addition, significant improvement was found in the global EQ-VAS (table 1) Conclusions: The tight control multidisciplinary rheumatology program is an efficient strategy to improve the QoL and the health perception of patients with chronic autoimmune diseases which impacts on the functionality, performance of everyday activities and productivity Reference: 1. Wang L, Wang FS, Gershwin ME. Human autoimmune diseases: A comprehensive update. Journal of Internal Medicine2015;278(2015):369–395. doi:10.1111/joim.12395 Disclosure of Interest: None declared